Albinism in the largest extant amphibian: A metabolic, endocrine, or immune problem? - Chang, Liming; Zhu, Wei; Jiang, Jianping (Frontiers in Endocrinology, 2022)
Pigment regression is an intriguing phenomenon which can be caused by disorders in melanin metabolism, endocrine regulation, and autoimmune. Albinistic animals provides excellent models to study the genetic determination of morphology, particularly the evolution and molecular mechanism of the chromatophore-related animal and human diseases. Artificial culture of A. davidianus, the largest extant amphibian, is flourishing in China due to the great ecological and economic value of this animal. Approximate 0.1% individuals have an albinistic phenotype accompanied with delayed somatic growth and mortality at early developmental stages. In this study, brain and skin transcriptomics was conducted to study the underlying molecular basis. Results indicated decreased transcription of genes of melanin synthesis. Interestingly, it is the MHC I isotypes and immune-related pathways accounted for the primary transcriptional differences between groups, suggesting that albinistic phenotype is a systematic immune problem far more than a pigmentation defect. Albinistic individuals have shifted transcription of MHC I isotypes, and the albinistic-specific isotype is featured by increased charges and decreased space in the antigen binding cave, implying drastic change of their antigen specificity and potential risk of autoimmune. These results suggest an association between abninistic phenotype and MHC I variants in A. davidianus, which can be a convenient model for the vitiligo or other autoimmune diseases.